Dari Limbah Kain Perca Menjadi Rupiah: Kolaborasi Kreatif dengan Bank Sampah di Desa Karangmojo Kabupaten Sukoharjo - Nuria Amanah, Aisah; Dini Dwi Puspita; Abdul Jabbar (Universitas Negeri Semarang, 2025)
Rag waste, left over from textile production, poses a serious environmental problem in Indonesia due to its difficulty in decomposing and its often-perceived lack of value. In an effort to address this issue, the UNNES Giat 9 team conducted a community service program in Karangmojo Village, Sukoharjo Regency, aimed at transforming rag waste into economically valuable products. This initiative involved the waste bank community